Bulimia nervosa in times of the COVID‐19 pandemic—Results from an online survey of former inpatients. (7th August 2020) - Schlegl, Sandra; Meule, Adrian; Favreau, Matthias; Voderholzer, Ulrich
Abstract: Objective: The COVID‐19 pandemic might pose special challenges to patients with eating disorders (EDs) by interfering with daily routines. The aim of this study was to investigate the impact of the current pandemic on patients with bulimia nervosa (BN). Methods: Fifty‐five former inpatients with BN completed an online survey on psychological consequences of the COVID‐19 pandemic as well as on changes in health care utilisation and on the use and helpfulness of different coping strategies. Results: Almost half of patients (49%) reported a deterioration of their ED symptomatology and 62% reported a reduced quality of life. The frequency of binge eating increased in 47% of patients and self‐induced vomiting in 36%. Forty‐six percent of patients stated a noticeable impairment of psychotherapy. Face‐to‐face psychotherapy decreased by 56% but videoconferencing therapy was only used by 22% of patients. Enjoyable activities, virtual social contacts with friends and mild physical activities were rated as the most helpful coping strategies among those most used. Discussion: Approximately one half to two‐thirds of former inpatients with BN experienced a negative impact of the crisis on their ED symptomatology and quality of life. In challenging times when face‐to‐face therapy options are restricted, e‐health treatments such as videoconferencing therapy should be considered to ensure continuity of care.